2016
DOI: 10.1093/ckj/sfw052
|View full text |Cite
|
Sign up to set email alerts
|

Intradialytic hypertension during chronic haemodialysis and subclinical fluid overload assessed by bioimpedance spectroscopy

Abstract: BackgroundIntradialytic hypertension (IDH) increases morbidity and mortality. The prevalence in South Africa is unknown. The pathogenesis is unclear, but it has been suggested that IDH may be due to subclinical fluid overload. The objective of this study was to determine the prevalence of IDH and to evaluate its association with fluid overload using bioimpedance spectroscopy (BIS).MethodsA cross-sectional study involving 190 chronic haemodialysis patients in the Western Cape province of South Africa was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
4
22
3
1
Order By: Relevance
“…The frequency of DHBP in our series was 40.5%. This frequency is close to that found in a study conducted in Cameroon [5] which reported a frequency of 48.3%, in Nigeria 45.3%, and in the Philippines 37% [11], but far higher than that found in the United States in 2018 with 5% -20% of treatments hemodialysis [6]; Italy in 2016 with 23.1% [12]; South Africa 28.4% [13]. In Senegal, it was 22.6% [7].…”
Section: Discussionsupporting
confidence: 83%
“…The frequency of DHBP in our series was 40.5%. This frequency is close to that found in a study conducted in Cameroon [5] which reported a frequency of 48.3%, in Nigeria 45.3%, and in the Philippines 37% [11], but far higher than that found in the United States in 2018 with 5% -20% of treatments hemodialysis [6]; Italy in 2016 with 23.1% [12]; South Africa 28.4% [13]. In Senegal, it was 22.6% [7].…”
Section: Discussionsupporting
confidence: 83%
“…However, our study includes objective measurements of ECV using the BIS equipment to establish this relationship along a more continuous spectrum of volume states. Our findings also significantly expand on 3 recent case-control studies, which showed that patients with intradialytic BP increases had more volume overload based on BIS measurements than those with intradialytic BP decreases [7, 8, 26]. However, our study establishes that the repeated measurements included in the IBPS provide superior information than just the change in systolic BP from pre- to post-HD and that one can predict the relative degree of ECV overload based on the IBPS.…”
Section: Discussionsupporting
confidence: 81%
“…This prevalence was comparable to that reported by Attilio [11] in Italy, which was 23.1%. However, it was lower than that of Sinomono [10] in Morocco, Sebastian [16] in South Africa and Mackanga [17] in Gabon, which reported prevalence rates of 29.17%, 28.4%, and 28.99% respectively. It was higher than that of the CLIMB study [18] as well asthe WAVE 2 study [19], which reported respective prevalence rates of 13.2% and 12%.…”
Section: Discussionmentioning
confidence: 67%